Comparison of the differential transformation method and non standard finite difference scheme for solving plant disease mathematical model - Meksianis Z. Ndii; Nursanti Anggriani; Asep K. Supriatna (Communication in Biomathematical Sciences, 2018)
The Differential Transformation Method (DTM) and the Non Standard Finite Difference Scheme (NSFDS) are alternative numerical techniques used to solve a system of linear and nonlinear differential equations. In this paper, we construct the DTM and NSFDS for a mathematical model of plant disease transmission dynamics and compare their solutions to that generated by MATLAB ode45 routine, which is the well-established numerical routine. The solutions of the DTM and NSFDS are in good agreement with MATLAB ode45 routine in the small time step. However, when the time step is larger, the NSFDS performs better than the DTM.